PENGARUH PENDIDIKAN DAN USIA KEHAMILAN TERHADAP KEJADIAN BAYI BERAT LAHIR RENDAH DENGAN IBU SECTIO CAESAREA (SC) DI RUMAH SAKIT UMUM DAERAH DR. PIRNGADI MEDAN - Juita, Chandra (Universitas Audi Indonesia, 2022)
BBLR (Low Birth Weight) is a baby whose weight is less than 2,500 grams without considering its gestation age. RSUD Dr. Pirngadi, Medan, in 2016 had the incidence rate of BBLR 30%, above the incidence of BBLR nationally (10.2%). The objective of the research was to find out some factors which influenced the incidence of BBLR. The research used observational analytic method with case control design. The samples were 160 that consisted of 80 sectio caesarean women with BBLR respondents in the case group and the other 80 sectio caesarean women with BBLN (Normal Birth Weight) in the control group, taken by using consecutive sampling technique. The data were gathered from medical records in the period of 2016-2017 with inclusion criteria and analyzed by using univariate analysis, bivariate analysis with chi square test The result of the research showed that there were influence of the incidence of BBLR on education (p=0.001; OR= 5,28 CI95% ( 2,02-13,79 and the age of pregnancy (p=0.001; OR=112.51 CI95% (14.89-849.82). It is recommended that health care providers provide health education for childbirth women by using immediate contraceptive device after giving birth, arranging birth intervals and the number of children by installing IUD(Intra Uterin Device) contraception in order not to disturb lactation process.